2017
DOI: 10.1089/thy.2016.0228
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death-Ligand 1 Expression in Papillary Thyroid Cancer and Its Correlation with Clinicopathologic Factors and Recurrence

Abstract: PD-L1 is important in determining aggressiveness of PTC and could predict the prognosis of patients. Therefore, inhibition of PD-L1 is suggested as a potential strategy for the treatment of advanced PTC with high expression of PD-L1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 36 publications
10
56
2
1
Order By: Relevance
“…PD-L1 expression in WDTC was reported as early as 2013 and was associated with aggressive features [48]. In papillary thyroid carcinoma, PD-L1 expression appears to occur in approximately 50% of tumors and is associated with decreased disease-free survival [43][49]. It is not clear what is responsible for the decreased rate of PD-L1 positivity in PDTC compared to PTC.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 expression in WDTC was reported as early as 2013 and was associated with aggressive features [48]. In papillary thyroid carcinoma, PD-L1 expression appears to occur in approximately 50% of tumors and is associated with decreased disease-free survival [43][49]. It is not clear what is responsible for the decreased rate of PD-L1 positivity in PDTC compared to PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding thyroid tumors, a few papers have reported on PD-L1 expression in thyroid (Cunha et al 2013, Angell et al 2014, Wu et al 2015, Bastman et al 2016, Chowdhury et al 2016, Ahn et al 2017, Shi et al 2017). With the exception of two studies on anaplastic (undifferentiated) thyroid carcinoma (ATC) (Wu et al .…”
Section: Dear Editormentioning
confidence: 99%
“…With the exception of two studies on anaplastic (undifferentiated) thyroid carcinoma (ATC) (Wu et al . 2015, Ahn et al 2017), these studies were focused primarily on follicular cell-derived tumors (differentiated thyroid carcinoma, DTC), including papillary thyroid carcinoma (PTC), follicular thyroid carcinoma (FTC) and poorly differentiated thyroid carcinoma (PDTC) (Cunha et al 2013, Angell et al 2014, Bastman et al 2016, Chowdhury et al 2016, Ahn et al 2017, Shi et al 2017). For these tumors (i.e., DTC), immunotherapy could be considered in the small minority of cases that are classed as refractory to radioiodine treatment.…”
Section: Dear Editormentioning
confidence: 99%
“…Furthermore, a log‐rank test failed to demonstrate PD‐L1 expression as a prognostic marker. Another study reported that PD‐L1 expression was present in 52.3% of PTCs . However, in contrast, positive PD‐L1 staining was linked to multifocality and extrathyroidal extension.…”
Section: Well‐differentiated Thyroid Carcinomamentioning
confidence: 99%
“…However, in contrast, positive PD‐L1 staining was linked to multifocality and extrathyroidal extension. Furthermore, PD‐L1 expression was associated with worse recurrence‐free survival . These studies highlight some of the challenges that pathologists and cytopathologists could face with the interpretation of PD‐L1 immunohistochemical stains.…”
Section: Well‐differentiated Thyroid Carcinomamentioning
confidence: 99%